METODE PENAFSIRAN AL-QUR’AN - Ahmad Haromaini (STAI Asy-Syukriyyah, 2015)
Qur'an into parts excellent guidelines for human life, it is because all aspects of life are discussed and described by him, however, the delivery conveyed the Qur'an to mankind not speak specifically but glonal. Keglobalannya, requires that Muslim scholars (ulama interpretation) busied itself to then take on a role in the explanation of these messages. Various methods ditempu by some scholars to present explanations interpretations, ranging methods tahlili, ijmali, muqarin and the latest is maudlu'i.